Assessing NH300094, a novel dopamine and serotonin receptor modulator with cognitive enhancement property for treating schizophrenia - Feng, Zijin; Hu, Zhijing; Li, Lei; Yu, Minquan; Zhang, Yiting; Jing, Peng; Xu, Xiangqing; Wu, Jinhui; Hu, Yiqiao; Xu, Xiangyang (Frontiers in Pharmacology, 2024)
Background: Schizophrenia is a serious psychiatric disorder that significantly affects the quality of life of patients. The objective of this study is to discover a novel antipsychotic candidate with highly antagonistic activity against both serotonin and dopamine receptors, demonstrating robust efficacy in animal models of positive, negative, and cognitive symptoms of schizophrenia. Methods: In the present study, we examined the activity of antipsychotic drug (NH300094) on 5-HT2A, 5-HT2C, 5-HT1A, 5-HT1B, 5-HT7, H1, M1, Alpha1A, D2L, D2S, Alpha2A, D3 receptor functional assay in vitro. In addition, multiple animal models, including dizocilpine (MK-801) induced hyper-locomotion; APO induced climbing; Conditioned Avoidance Response (CAR); DOI-Induced Head Twitch; Forced swimming test; Scopolamine induced cognitive impairment model, were used to verify the antipsychotic activity of NH300094 in preclinical. Results:In vitro functional assays have indicated that NH300094 is a potent antagonist of 5-HT receptors and dopamine receptors, with higher relative antagonistic activity against 5-HT2A receptor (5-HT2A IC50 = 0.47 nM) than dopamine receptors (D2L IC50 = 1.04 nM; D2S IC50 = 11.71 nM; D3 IC50 = 31.55 nM). Preclinical in vivo pharmacological study results showed that NH300094 was effective in multiple models, which is more extensive than the clinic drug Risperidone. Furthermore, the safety window for extrapyramidal side effects of NH300094 is significantly wider than that of Risperidone (For NH300094, mice catalepsy model ED50/ Mice MK-801 model ED50 = 104.6-fold; for Risperidone, mice catalepsy model ED50/ Mice MK-801 model ED50 = 12.9-fold), which suggests a potentially better clinical safety profile for NH300094. Conclusion: NH300094 is a novel potent serotonin and dopamine receptors modulator, which has good safety profile and therapeutic potential for the treatment of schizophrenia with cognition disorders.